Microbial community characteristics and environmental response of water bodies in different environmental areas underground coal mine - Haitao ZHANG; Guangquan XU; Xiaoqing CHEN; Xu LI; Zixuan LI; Yanxi ZHANG; Gang ZHANG; Jianghui HE (Meitan xuebao)
To explore the microbial community characteristics and their response to environmental factors in different environmental areas of an underground coal mine, a study was conducted in the Xieqiao coal mine in Huainan, Anhui. A total of 24 water samples were collected from eight underground environmental areas involved in the entire process of mine water sourcing, formation, and accumulation, including the shaft, rock roadway, coal roadway, coal face, goaf, sump, sandstone water outflow point, and limestone water discharge point. These samples underwent hydrochemical composition analysis and high-throughput sequencing of the 16S rRNA gene. Multivariate statistical methods were employed for sequence data processing. The results showed that ① the shaft water is of Cl-Na·Ca type, the sandstone water and goaf water are of HCO3·Cl-Na type, and the other areas are all of Cl-Na type. Significant variations were observed in the concentrations of Na+, Cl−, \begin{document}${SO}_4^{2-} $\end{document}, \begin{document}${HCO}_3^- $\end{document}, \begin{document}${NO}_2^- $\end{document}, \begin{document}${NO}_3^- $\end{document}, and Fe among the different environmental areas waters. ② The microbial richness and diversity were highest in the sump water and lowest in the rock roadway water. A total of 55 bacterial phyla and 621 genera were detected across the 24 samples, with Pseudomonadota, Bacteroidota, and Nitrospinota as the dominant phyla, and Hydrogenophaga and Pseudomonas as the dominant genera. Pseudomonadota had the highest abundance in the rock roadway water and the lowest in the limestone water; Bacteroidota were most abundant in the sump water and least in the rock roadway water; Nitrospinota were most abundant in the limestone water and least in the rock roadway water. Hydrogenophaga showed a relatively high abundance across all environmental areas waters, while Pseudomonas was mainly distributed in the rock roadway water. ③ The underground microbial community structure and distribution in the coal mine were primarily influenced by pH, followed by nutrients such as C, N, and S, temperature, DO, ORP, and redox-sensitive substances like Fe, Mn, and Sb. ④ FAPROTAX analysis indicated that the microbial communities in this coal mine exhibited general functions of chemoheterotrophy and aerobic chemoheterotrophy. The microbial communities in water bodies of different environmental areas exhibited diverse ecological functions, ranging from basic metabolic activities such as material cycling and energy conversion to complex environmental remediation processes such as pollutant degradation and water quality improvement. These functions maintained the ecological balance of underground water bodies in coal mines and played an important role in regulating and restoring ecosystems.